Pelatihan Kewirausahaan Berbasis Iptek untuk Membina Ibu Rumah Tangga yang Produktif di Kelurahan Lolong-Belanti, Padang - Prima Fithri; Lusi Susanti; Difana Meilani; Suci Rahmawati; Ulfa Nadiatur Rahmi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2020)
The polemic of unemployed women is getting worse because in choosing a job, women often think about work that does not interfere with their routine as housewives. In addition, there is also a labor market that does not accept female workers, either single or married, for reasons that are sometimes illogical. Even though the abilities and skills of women are no less good and there are no differences with men. This is also a major factor why many women are unemployed. As a result, it becomes a factor of poverty. Given the importance of this problem, it is necessary to implement ways to overcome them, especially in reducing the number unemployment. The solution to this problem is quite easy, as long as it is given a job, the unemployment problem will be resolved. However, in practice it is not that easy. To open new jobs requires substantial funds, in addition to funds, it is necessary to provide entrepreneurship training for the unemployed so that the unemployed have skills capital in the world of work to be involved. As a scientific discipline, entrepreneurship can be studied and taught, so that every individual has the opportunity to appear as an entrepreneur (entrepreneur). Even to be a successful entrepreneur, having talent is not enough, you also need to have knowledge of all aspects of the business that you will be engaged in. The tasks of entrepreneurship are very many, including the task of making decisions, technical leadership, and leadership, therefore facilities and infrastructure are needed, one of which is education.